Powering up China: Income Distributions and Residential Electricity Consumption - Auffhammer, Maximilian; Wolfram, Catherine D. (American Economic Review, 2014)
Current forecasts suggest that the vast majority of growth in energy demand will come from the developing world, and that China will play a major part in that growth. This paper presents evidence suggesting that the shape of the income distribution, which is typically omitted from forecasting models, plays a major role in driving household acquisition of energy-using durable goods in rural China. We use province-level data for rural households to show that the share of the population living above the poverty line is an important determinant of household appliance holdings even controlling for average household income.